Observations of transients and pulsars with LOFAR international stations - Serylak, M; Karastergiou, A; Williams, C; Armour, W; Group, LOFARPW (2012)
The LOw FRequency ARray - LOFAR is a new radio telescope that is moving the science of radio pulsars and transients into a new phase. Its design places emphasis on digital hardware and flexible software instead of mechanical solutions. LOFAR observes at radio frequencies between 10 and 240 MHz where radio pulsars and many transients are expected to be brightest. Radio frequency signals emitted from these objects allow us to study the intrinsic pulsar emission and phenomena such as propagation effects through the interstellar medium. The design of LOFAR allows independent use of its stations to conduct observations of known bright objects, or wide field monitoring of transient events. One such combined software/hardware solution is called the Advanced Radio Transient Event Monitor and Identification System (ARTEMIS). It is a backend for both targeted observations and real-time searches for millisecond radio transients which uses Graphical Processing Unit (GPU) technology to remove interstellar dispersion and detect millisecond radio bursts from astronomical sources in real-time using a single LOFAR station.